Synthesis And Molecular Docking Studies Of New Phenylisoxazole Quinoxaline-2-Amine Hybrids As Potential Α Amylase And Α-Glucosidase Inhibitors - Radzuan, Siti Nurshahira Mohd (2024)
New phenylisoxazole quinoxaline-2-amine hybrids 55a-i were successfully synthesised with percentage yield ranging from 53% to 85%. These compounds were purified and characterised by 1D- and 2D- NMR (1H, 13C, HSQC, HMBC and COSY), FTIR, and HRMS analyses. Then, the hybrids underwent in vitro α-amylase and α-glucosidase inhibitory assays, with acarbose as the positive control. Through the biological study, compound 55i exhibits the most potent α-amylase inhibitory activity with IC50 = 16.4 M, while compounds 55a, 55c-f, and 55i exhibit good potential as α-glucosidase inhibitors, with 55e being the most potent inhibitor (IC50 = 15.2 M). Moreover, through the molecular docking studies, the inhibition potential for both α-amylase and α-glucosidase were affirmed, where all selected compounds exhibit good binding energy with both enzymes. Compound 55i showed important interactions with α-amylase enzyme active site and exhibited the highest binding energy of -8.9  0.10 kcal/mol, while compound 55e exhibited the highest binding energy of -9.0  0.20 kcal/mol by forming important interactions with the α-glucosidase enzyme active site residues. From the in vitro and in silico studies conducted, it can be concluded that compounds 55c and 55i exhibit the potential as dual inhibitors for both enzymes. Thus, it can be concluded that the quinoxaline-isoxazole hybrids synthesised in this study exhibit promising potential as α-amylase and α-glucosidase inhibitors for type 2 diabetes mellitus.